Experimental investigation on partial discharge characteristics of epoxy-nanocomposite as hight voltage insulation material - Hasan Rhaif, Suhad (2014)
In electrical engineering, electrical discharge can occur in gaseous, liquid or solid insulating medium. Localized dielectric breakdown that occur at a small portion of a solid or fluid electrical insulation under high voltage stress is called partial discharge (PD). As such, it is important to study about PD. Usually it begins within voids, cracks, or inclusions within a solid dielectric, at conductor-dielectric interfaces within solid and in bubbles within liquid dielectrics. In order to modify electrical properties of the original structure then nano composite need to be introduced. Nano composite is the original structure that has been inserted by nano component (nano filler) such as Boron nitride. By adding nano component inside the original component, it can change the mechanical and electric properties. In this project, partial discharge characteristics for the nano composites will be investigated. The sample of nano composite was developing by using mixing method the sample will be testing by using detection method. High voltage is applied at the upper of the electrode of the test sample. Partial discharges pulses were detected by a DDX-9101 and measured using a personal computer-based partial discharge measurement system. The result from the software will be analyst to find out the partial discharge of the nano composites as electric insulating material. The objective of this study is to conduct an experimental investigation of partial discharge (PD) characteristics of Epoxy-nano composite material as electrical insulation.. The effect of nano filler content and amount in the nano composite sample will be investigated. The number PD, PD charge magnitude, and average of PD charge during the ageing time will be investigated. Physical properties such as degradation morphology of tested samples by using optical microscope techniques before and after ageing. Investigation will also be performed in order to obtain comprehensive results